In Silico Evaluation of Typhonium flagelliforme Fatty Acids for Cdc25B Inhibition and Chemotherapy Synergistic Potential - Lisnasari, Baiq Risky; Maulidya, Selvira Anandia Intan (Jurnal Biologi Tropis, 2025)
Typhonium flagelliforme exhibits cytotoxic activity against various cancer cell lines, including breast cancer. This study employed an in silico approach to evaluate the potential interaction or synergy between its fatty acid derivatives—2-octenoic acid and 2-hexenoic acid—and standard cytotoxic agents in breast cancer therapy. SwissTargetPrediction was used to identify the putative molecular targets of the compounds. Molecular docking was performed against phosphatase Cdc25B (PDB ID: 1CWR) using CB-Dock2, and pharmacokinetic properties were evaluated using SwissADME. Both 2-octenoic acid and 2-hexenoic acid were predicted to target Cdc25A and Cdc25B, which are key regulators of cell cycle progression. Molecular docking revealed binding affinities of −4.42 and −4.60 kcal/mol, respectively, compared to −5.97 kcal/mol for the native inhibitor NSC 663284. These compounds shared multiple key residues in the binding pocket, although they formed fewer hydrogen bonds. Pharmacokinetic predictions showed high gastrointestinal absorption, blood–brain barrier permeability, and no inhibition of major cytochrome P450 enzymes, suggesting minimal interaction with the metabolic pathways of standard chemotherapeutics. The results suggest that T. flagelliforme metabolites may not interfere with cytotoxic drug metabolism but could provide a synergistic effect by targeting cell cycle regulators.